Almost Semi-extending Modules - Ahmed, Muna Abbas; Abbas, Maysaa Riadh; Adeeb, Noor Riyadh (Iraqi Journal of Science, 2022)
Fuchs introduced purely extending modules as a generalization of extending modules. Ahmed and Abbas gave another generalization for extending modules named semi-extending modules. In this paper, two generalizations of the extending modules are combined to give another generalization. This generalization is said to be almost semi-extending. In fact, the purely extending modules lies between the extending and almost semi-extending modules. We also show that an almost semi-extending module is a proper generalization of purely extending. In addition, various examples and important properties of this class of modules are given and considered. Another characterization of almost semi-extending modules is established. Moreover, the relationships with other related concepts are studied and discussed